Principle, design and validation of a power-generated magnetorheological energy absorber with velocity self-sensing capability. (13th June 2018) - Bai, Xian-Xu; Zhong, Wei-Min; Zou, Qi; Zhu, An-Ding; Sun, Jun
Abstract: Based on the structural design concept of 'functional integration', this paper proposes the principle of a power-generated magnetorheological energy absorber with velocity self-sensing capability (PGMREA), which realizes the integration of controllable damping mechanism and mechanical energy-electrical energy conversion mechanism in structure profile and multiple functions in function profile, including controllable damping, power generation and velocity self-sensing. The controllable damping mechanism consists of an annular gap and a ball screw. The annular gap fulfilled with MR fluid that operates in pure shear mode under controllable electromagnetic field. The rotational damping torque generated from the controllable damping mechanism is translated to a linear damping force via the ball screw. The mechanical energy-electrical energy conversion mechanism is realized by the ball screw and a generator composed of a permanent magnet rotor and a generator stator. The ball screw based mechanical energy-electrical energy conversion mechanism converts the mechanical energy of excitations to electrical energy for storage or directly to power the controllable damping mechanism of the PGMREA. The velocity self-sensing capability of the PGMREA is achieved via signal processing using the mechanical energy-electrical energy conversion information. Based on the principle of the proposed PGMREA, the mathematical model of the PGMREA is established, including the damping force, generated power and self-sensing velocity. The electromagnetic circuit of the PGMREA is simulated and verified via a finite element analysis software ANSYS. The developed PGMREA prototype is experimentally tested on a servo-hydraulic testing system. The model-based predicted results and the experimental results are compared and analyzed.